Pandangan Orientalis Terhadap al-Hadith dan Jawapannya dari Perspektif Islam - Abd. Rahman, Mohd. Muhiden (Jurnal Usuluddin, 1997)
The article tries to survey Western Orientalists perceptions on al-Hadith. It attempts to examine the Orientalists' views on al-Hadith as well as the 'Isnad System' (chain of transmitter) as a mechanisme in accepting and scrutinizing the soundness of a Hadith. The discussion ends up with answers as advanced by Muslim scholars against the Orientalists' critical view.